Highly Selective Cycloalkane Oxidation in Water with Ruthenium Nanoparticles. Issue 2 (18th November 2015) - Denicourt‐Nowicki, Audrey; Lebedeva, Anastasia; Bellini, Clément; Roucoux, Alain
Abstract: Ruthenium(0) nanospecies, with small sizes of approximately 1.75 nm, proved to be active, selective, and retrievable nanocatalysts for the oxidation of various cycloalkanes in neat water, using tert ‐butylhydroperoxide as an oxidant and at room temperature. Relevant conversions and selectivities (up to 97 %) were achieved towards the major formation of the ketone product, which constitutes a high‐value‐added intermediate for polymer or fine chemistry. The lifetime of the catalyst has been checked over several runs, with no significant loss of activity and selectivity. Kinetic and mechanistic investigations proved that radical species are involved in the oxidation process. A literature comparison showed the relevance and the usefulness of the present ruthenium nanocatalytic system in a benign reaction context. Abstract : Active, selective, and retrievable ! A sustainable oxidation process of cycloalkanes to the ketones with an easy‐to‐handle and reusable catalyst, in neat water, and under ambient conditions is described. The active catalyst is a ruthenium(0) nanospecies. t ‐BHP= tert ‐butylhydroperoxide.